Efficacy evaluation of using hypoallergenic toothpastes in children with a burdened allergy anamnesis - I. D. Kondratenko; I. A. Nikolskaya; R. M. Kuliev; V. O. Vostrikov; V. A. Voronetskaya; A. Novikova (Эндодонтия Today)
Aim. To conduct a clinical evaluation of the efficacy of using hypoallergenic children's toothpastes “R.O.C.S. PRO Baby" and "R.O.C.S. PRO Junior Creamy Pudding" in patients aged 2 to 11 years with a burdened allergy history.   Materials and methods. The study included 58 children aged 2 to 11 years with a burdened allergy history. Before the start of the study, they were divided into two groups: the first included 28 children aged 2-3 years, whose parents had been brushing their teeth with « R.O.C.S. PRO Baby» hypoallergenic paste for 3 months. The second group included 30 childrenaged 6-11 years who provided oral care using the paste « R.O.C.S. PRO Junior Cream pudding ». During the control dental examinations, the determination of the possible locally irritating and allergenic effects of the studied toothpastes was carried out by visual examination of the oral mucosa of patients of both groups, as well as interviews and questionnaires of study participants and their parents. In patients of the second group, the hygienic condition of the oral cavity was assessed by determining the PHP hygiene index, PMA and SBI indices to assess the condition of periodontal tissues.   Results. During the study, patients with a burdened allergy history did not have a locally irritating and allergenic effect of hypoallergenic toothpastes "R.O.C.S. PRO Baby" and "R.O.C.S. PRO Junior Cream pudding" on the oral mucosa. When using toothpastes, there was a significant decrease in the PHP, PMA and SBI indices by 58.47 %, 47.4 % and 43.2 %, respectively.   Conclusions. The obtained data allow us to conclude that hypoallergenic toothpastes « R.O.C.S. PRO Baby » and « R.O.C.S. PRO Junior Creamy Pudding » meets the safety and efficacy criteria for cleaning teeth and can be recommended to patients with a history of allergies aged 2 to 11 years for daily hygienic oral care.